Examining the lived cultural experiences of veterans at military-friendly community colleges: a narrative inquiry - Miller, Matthew E. (My University, 2025)
Military veterans represent a unique community college demographic with a powerful cultural background that informs their approaches to learning, campus interactions, and challenge negotiation styles. Community colleges place a special emphasis on recognizing the cultural background of veterans and tailor support services and campus resources to embrace culturally specific inclusivity philosophies. These philosophies manifest as campus resource centers, targeted student support frameworks, and inclusive practices that recognize the important influence of culture on the military veteran student experience. The purpose of this qualitative narrative inquiry study was to explore the lived cultural experiences of veterans at a military friendly community college. This study was an exploration of a challenging student experience that is influenced heavily by powerful cultural background considerations and highlights the cultural implications associated with difficulties and successes. This study found that challenges with transition from military to community college student, interpersonal relationships, and campus acclimation have foundations in military culture. Successful use of skills gained from military culture was vital to veteran student success and influenced military student behaviors and attitudes positively. By identifying specific cultural experiences and their implication on the student experience, this study established direct evidence of a cultural confluence that complicates the military veteran community college journey.
Keywords: Military; Veterans; Community college